2012
DOI: 10.1158/1538-7445.am2012-4504
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 4504: Retrospective study of clinicopathologic factors associated with ALK rearrangement and survival outcome in Chinese patients with NSCLC

Abstract: Background: ALK rearrangement and EGFR mutation are significant molecular subtypes of non-small cell lung cancer (NSCLC) that are targets for different tyrosine kinase inhibitors (TKIs). We tested a large cohort of NSCLC patients for ALK, EGFR and KRAS abnormalities and correlated clinical factors with the ALK fusion gene and overall survival (OS). Methods: ALK status was detected by RACE sequencing; EGFR and KRAS status were also detected by direct DNA sequencing. OS was estimated by the Kaplan-Meier method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…While some previous research (Zhang et al 24 , for example) has shown no survival difference in metastatic nsclc by alk status (after adjustments for initial disease stage, histology, and egfr/kras mutation), a majority of studies (including a recent review article by Kulig et al 25 ) have reported a poorer survival prognosis for patients with alk-mutated (vs. wild type) tumours independent of alk-inhibitor treatment. Further research is needed, however, to more fully clarify the role of alk rearrangement independent of treatments on the survival prognosis of patients with metastatic nsclc.…”
Section: Discussionmentioning
confidence: 95%
“…While some previous research (Zhang et al 24 , for example) has shown no survival difference in metastatic nsclc by alk status (after adjustments for initial disease stage, histology, and egfr/kras mutation), a majority of studies (including a recent review article by Kulig et al 25 ) have reported a poorer survival prognosis for patients with alk-mutated (vs. wild type) tumours independent of alk-inhibitor treatment. Further research is needed, however, to more fully clarify the role of alk rearrangement independent of treatments on the survival prognosis of patients with metastatic nsclc.…”
Section: Discussionmentioning
confidence: 95%
“…In two separate reports [65, 95], Shaw et al did not demonstrate any significant differences in overall survival (OS) for patients with NSCLC by EML4-ALK status in the era before crizotinib. Similarly, Zhang et al reported no survival difference according to ALK status after adjusting for disease stage, histology, and EGFR/KRAS mutant status [101]. Lee et al showed that patients with ALK-rearranged NSCLC had the shortest overall survival compared to wild-type patients, but the difference was not significant [102].…”
Section: Clinicopathologic Characteristics Of In Patients With Alk-rementioning
confidence: 99%